BRANDING THE NORTH CAROLINA MUSEUM OF ART : PLANNING AND IMPLEMENTING A PUBLIC IDENTITY - Cranford, Christine (East Carolina University, 2013)
This dissertation examines the North Carolina Museum of Art's planning and implementation of a brand identity. To understand the planned identity, I studied the intentions of the Museum's leadership, of the architect who designed the new West Building, as well as the intentions of the NCMA staff whom I interviewed to understand their revisions of the Positioning Statement and redesign of the logo and accompanying alphabet by a design agency. Then to determine the brand identity being implemented by NCMA, I analyzed a campaign brochure created following the revision of the Positioning Statement and the visuals used on selected web pages; to begin to perceive how the public views the new branding initiative, analyzed public comments posted on tripadvisor and Yelp* websites. The Marketing Department sought a brand identity for NCMA as a museum that offers a multi-tiered experience for the people of North Carolina. Studying the branding initiative of the North Carolina Museum of Art reveals that the characteristics of the brand identity the Museum's professionals planned to create aligns closely with those of the brand identity being implemented in promotional materials since the opening of the West Building in April 2010.
Keywords: Technical communication; Marketing; Museum studies; Identity; Professional discourse; North Carolina Museum of Art; Art museums--Public relations--North Carolina; Branding (Marketing)--North Carolina